Network Pharmacology and Experimental Assessment to Explore the Pharmacological Mechanism of Qimai Feiluoping Decoction Against Pulmonary Fibrosis - Yang, Yingying; Ding, Lu; Bao, Tingting; Li, Yaxin; Ma, Jing; Li, Qingwei; Gao, Zezheng; Song, Siyu; Wang, Jing; Zhao, Jiachao; Wang, Ziyuan; Zhao, Daqing; et al. (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis (PF) is one of the pathologic changes in COVID-19 patients in convalescence, and it is also a potential long-term sequela in severe COVID-19 patients. Qimai Feiluoping decoction (QM) is a traditional Chinese medicine formula recommended in the Chinese national medical program for COVID-19 convalescent patients, and PF is one of its indications. Through clinical observation, QM was found to improve the clinical symptoms and pulmonary function and reduce the degree of PF of COVID-19 convalescent patients. To further explore the pharmacological mechanisms and possible active components of QM in anti-PF effect, UHPLC/Q-TOF-MS was used to analyze the composition of QM extract and the active components that can absorbed into blood, leading to the identification of 56 chemical compounds and 10 active components. Then, network pharmacology was used to predict the potential mechanisms and targets of QM, it predicted that QM exerts its anti-PF effects via the regulation of epithelial–mesenchymal transition (EMT), extracellular matrix (ECM) degradation and TGF-β signaling pathway. Finally, TGF-β1-induced A549 cells were used to verify and explore the pharmacological efficacy of QM and found that QM could inhibit the proliferation of TGF-β1-induced A549 cells, attenuate EMT and promote ECM degradation by inhibiting TGF-β/Smad3 pathway.